Rethinking Auditor Independence: Evidence from High-Corruption Environments - Bambang Setiono; Seng Hansen (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This study re-examines the concept of auditor independence in high-corruption environments, arguing that independence is not merely a professional attribute, but an outcome constrained by multilevel institutional, organizational, and individual pressures.Methodology: The study identifies the determinants of auditor behaviour through a survey analysed using exploratory factor analysis (EFA).Finding: We identify eleven interrelated factors shaping auditor behaviour, which cluster into three dimensions: (1) Capability and Stance, (2) Alignment and Resourcing, and (3) Protection and Pressure. The findings suggest that auditors operate not as fully independent monitors but as constrained agents embedded within corruption-prone systems, where institutional pressures, organizational incentives, and personal risks jointly shape audit outcomes.Conclusion: This study shifts the conceptualization of auditor independence from an assumed professional condition to a context-dependent outcome. By integrating agency, fraud-triangle, and institutional perspectives, we show that the audit expectation gap reflects structural constraints rather than mere misunderstanding of auditor roles.